Pengaruh Media Pembelajaran Digital “Aplikasi Quizizz “ Terhadap Motivasi Belajar Murid Pada Pembelajaran IPAS di SDN 3 Mangkalaya Kabupaten Sukabumi - Eneng Serli; Arnie Fajar; Eneng Martini (EDUKASI, 2026)
This study aims to analyze the effect of using the Quizizz digital learning application on students’ learning motivation in elementary school IPAS (Integrated Science and Social Studies) learning. This research employed a quantitative approach with a descriptive-verificative design. The population consisted of all upper-grade students at SD Negeri 3 Mangkalaya, Sukabumi Regency, in the 2025/2026 academic year, totaling 159 students, with a sample of 20 students selected proportionally. Data were collected using Likert-scale questionnaires and observation, and analyzed through descriptive and inferential statistics, including simple linear regression and t-test. The results indicate that the use of Quizizz has a positive and significant effect on students’ learning motivation, with a correlation coefficient of 0.892 and a contribution of 79.6%. In addition, Quizizz also positively influences students’ perseverance (79.5%), activeness (67.0%), and engagement (62.0%) in learning activities. These findings suggest that gamification-based digital learning media effectively enhance students’ overall learning motivation. In conclusion, Quizizz can be utilized as an effective and innovative instructional strategy to improve students’ learning motivation in elementary education. This study implies that the integration of digital technology in learning should be continuously developed to create more interactive, engaging, and student-centered learning environments.